Integrative metabolome and genome-wide transcriptome analyses reveal the regulatory network for bioactive compound biosynthesis in lettuce upon UV-A radiation - Lingyan Zha; Shiwei Wei; Xiao Yang; Qingliang Niu; Danfeng Huang; Jingjin Zhang (Molecular Horticulture)
Abstract Ultraviolet A (UV-A) radiation possesses great potential for enhancing the bioactive properties of vegetables and also has promising application prospects in controlled-environment agriculture. Lettuce is a widely cultivated model vegetable in controlled-environment agriculture with abundant health-beneficial bioactive compounds. However, the comprehensive regulatory effectiveness and mechanism of UV-A on bioactive compounds in lettuce remain largely unclear. To address this issue, we performed transcriptomic and metabolomic analyses of UV-A-treated lettuce to construct a global map of metabolic features and transcriptional regulatory networks for all major bioactive compounds. Our study revealed that UV-A promotes the accumulation of most phenylpropanoids and vitamins (provitamin A and vitamin E/K1/B6) but represses the biosynthesis of sesquiterpenoids. MYB transcription factors (TFs) are key activators of bioactive compound biosynthesis promoted by UV-A, whereas WRKY TFs primarily inhibit the production of sesquiterpenoids. Moreover, light signaling plays a crucial and direct regulatory function in stimulating the biosynthesis of phenylpropanoids and vitamins but not in that of sesquiterpenoids. In comparison, hormone signaling dominates a more decisive regulatory role in repressing sesquiterpenoid biosynthesis through working directly and interacting with WRKY TFs. This study paves the way toward an understanding of the bioactive compound regulation and genetic improvement of lettuce bioactivity value.